Covid-19 o el desvelador silente - Peralta Núñez, Cristian Rafael (My University)
El COVID-19 ha puesto en evidencia las precariedades de muchos países, pero también las preocupaciones de los intelectuales que han comentado la situación actual, olvidando los contextos de pobreza, desigualdad y exclusión social.

COVID-19 has highlighted the precariousness of many countries, but also the concerns of intellectuals who have commented on the current situation, forgetting the contexts of poverty, inequality and social exclusion.
Artículo en Periódico